FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA DENGAN GCG SEBAGAI VARIABEL MODERASI - Regina; Herlin Tundjung Setijaningsih (Fakultas Ekonomi Universitas Tarumanagara, 2023)
This research aims at how the role of the free cash flow, financial distress and leverage on earning management, and the effect of good corporate governance as moderating toward earning management on manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 321 companies. Data processing techniques using moderated regression analysis what helped by Eviews program Version 12.0 and Microsoft Excel 2019. The results of this study indicate that financial distress and leverage have no significant influence on earning management, free cash flow has a negative and significant influence on earning management and GCG in this study is able to moderate the influence of free cash flow on earning management but GCG is not able to moderate the influence of financial distress and leverage on earnings management.